Learning Tahfiz Al-Quran at Islamic Boarding School - Khoiriyah, Hapsah; Hanum, Azizah; Nahar, Syamsu (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This study aimed to describe the Tahfiz learning system at Ma'had Tahfiz Maryam Al-Khol Al-Fityan School Medan. This research was qualitative with a case study approach. The research data was in the form of learning tahfiz at Ma'had tahfiz Maryam Al-Khol Al-Fityan School Medan. Observation, interviews, and documentation carry out data collection techniques. In contrast, data analysis was done by data reduction, presentation, conclusion, and verification. There were four findings in this study, namely: (1) The planning of the Tahfiz learning system at Ma'had Tahfiz Maryam Al-Khol Al-Fityan School Medan is by planning Tahfiz learning programs as daily planning programs, weekly planning programs, and monthly planning programs. (2) Implementation with several stages of implementation in Tahfiz learning planning. Develop the needs needed, and play an active role in every policy made. (3) Internal evaluation is an evaluation carried out by the head of the department within the organization itself. (4) The supporting factors are the target memorization and the environment. The obstacle was the limited human resources of educators. The solution was to provide training programs and develop educational competencies and teaching methods and Al-Qur'an memorization, motivating students to memorize the Al-Qur'an and strict supervision of students.